2023
DOI: 10.1167/iovs.64.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol Attenuates Form Deprivation Myopia Through a Signaling Pathway Parallel to TGF-β2–Induced Increases in Collagen Expression

Abstract: Purpose To determine the role of calcipotriol, a vitamin D3 analogue, in myopia development and altering the expression of scleral α1 chain of type I collagen ( Col1α1 ) in mice. We also aimed to identify if the signaling pathway mediating the above changes is different from the one involved in transforming growth factor β2 (TGF-β2)–mediated increases of COL1A1 in cultured human scleral fibroblasts (HSFs). Methods C57BL/6J mice were either int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Calcitriol can alleviate scleral collagen degradation and change the arrangement of scleral collagen. We speculate that calcitriol may mediate this effect through VDR 26 www.nature.com/scientificreports/ progression but also contributes to the thickening of the choroid and sclera, along with an increase in scleral collagen diameter, providing substantial evidence for the development and application of myopia-preventative pharmaceuticals.…”
Section: Discussionmentioning
confidence: 97%
“…Calcitriol can alleviate scleral collagen degradation and change the arrangement of scleral collagen. We speculate that calcitriol may mediate this effect through VDR 26 www.nature.com/scientificreports/ progression but also contributes to the thickening of the choroid and sclera, along with an increase in scleral collagen diameter, providing substantial evidence for the development and application of myopia-preventative pharmaceuticals.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, a Dutch study of 6-year-old children showed an association between myopia and high BMI ( 25 ). Obesity often leads to a variety of complications, and one factor associated with myopia is insulin resistance ( 25 , 26 ). Insulin resistance is one of the most common biochemical phenomena associated with obesity, and the suppression of insulin secretion in hyperglycemic states leads to lens thickening, anterior pole shift, and worsening myopia ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most recent studies, which aimed to explore the function of vitamin D 3 in myopia development, was carried out on mice. Calcipotriol (a vitamin D 3 analogue) apparently triggers a signaling pathway dependent on the scleral vitamin D receptor, elevating the levels of α1 chain of type I collagen expression in the sclera [ 13 ]. Regarding younger children (aged 5–15 years), there appears to be no remarkable connection between vitamin D deficiency and myopia [ 14 ].…”
Section: Myopiamentioning
confidence: 99%